Education on the Importance of the First 1000 Days of Life in an Effort to Improve the Nutritional Status of Children in the Working Area of Kartini Public Health Center, Pematang Siantar City - Yunardi (PT Inovasi Pratama Internasional, 2022)
Activity devotion to public Which held form education the importance of the First 1000 Days of Life in improving health status and child nutrition in the Work Area Kartini Health Center, Pematang Siantar City. Partners in this activity is the Kartini Community Health Center with the target being pregnant women and mothers toddlers who come to Posyandu in the Work Area of the Kartini Health Center in City Siantar District. Election location activity is Because Public health center Kartini is Wrong One Public health center Which there is in center city Siantar District. Problems nutrition And health especially on toddler can prevented through activity education Which given through activity Integrated Healthcare Center. Solution Which done in activity devotion to public form give education 1000 Day First Life to parent toddler specifically moms Which come visit to Integrated Healthcare Center. Objective activity dedication is to increase the knowledge of parents of toddlers about 1000 First Day of Life and changes in good nutritional behavior so that it can improve the health and nutritional status of children. The benefit of this activity is that Parents especially pregnant women and toddler mothers know the importance of 1000 Day First Life For prevent happening problem nutrition on toddler And increase health status And nutrition child. The expected output of community service activities is in the form of published articles in journal devotion And leaflet .